IMPLIKASI SELF EFFICACY TERHADAP PERENCANAAN KARIER SISWA - Mujiyati, Mujiyati (STKIP Muhammadiyah Pringsewu, 2016)
This study is carried out due to less of students understanding about future career planning, whereas those students have enough self belief about their potential. Therefore this study aims to know the strength of relation between self efficacy and studentsâ career planning. This study used quantitative approach that emphasize on numerical data of behavior which is processed by statistics method. This study used correlational statistic design. Product moment was employed in this research. The result shows positive correlation between self efficacy and career planning of the tenth grade students of Senior High School Yasmida Ambarawa, in even semester 2014/2015. Based on the result, this research contribution consists of career planning 65.52% was influenced by self efficacy and the rest 34.34% was influenced by others. In conclusion, if someone improve self efficacy in career, their career planning will improve too.Key Words: Correlation, sefl efficacy, and career plannning.